2012
DOI: 10.1109/led.2012.2192712
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage Oxide-Based Electric-Double-Layer TFTs Gated by Stacked $\hbox{SiO}_{2}$ Electrolyte/Chitosan Hybrid Dielectrics

Abstract: Low-voltage oxide-based electric-double-layer (EDL) thin-film transistors (TFTs) gated by stacked SiO 2 electrolyte/chitosan proton-conductor hybrid dielectric have been fabricated on glass substrates at room temperature. Such EDL TFTs exhibit a saturation mobility (μ sat ) of 7.8 cm 2 · V −1 · s −1 , a subthreshold swing (S) of 100 mV/decade, a drain current ON/OFF ratio (I on/off ) of 7.8 × 10 5 , and a threshold voltage (V th ) of −0.48 V. After aging for one month in air ambient without surface passivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…It is observed that the capacitance decreased when the frequency is increased from 1.0 Hz to 1.0 MHz. The high capacitance (2 µF/cm 2 ) obtained at a low frequency is attributed to the formation of an EDL at the AZO electrode/SA membrane interface [6]- [10]. We also obtained an acceptably low leakage current for the SA membrane with the in-plane AZO-SA-AZO structure of below 60 pA at an applied voltage of 1 V (See Fig.…”
Section: Experiments Detailsmentioning
confidence: 54%
“…It is observed that the capacitance decreased when the frequency is increased from 1.0 Hz to 1.0 MHz. The high capacitance (2 µF/cm 2 ) obtained at a low frequency is attributed to the formation of an EDL at the AZO electrode/SA membrane interface [6]- [10]. We also obtained an acceptably low leakage current for the SA membrane with the in-plane AZO-SA-AZO structure of below 60 pA at an applied voltage of 1 V (See Fig.…”
Section: Experiments Detailsmentioning
confidence: 54%
“…Such materials can be obtained in solid-state forms, but they usually exhibit poor chemical stability particularly at elevated temperatures 16 . Oxide-based solid-state electrolytes, such as porous SiO 2 and Al 2 O 3 , have also emerged as an alternative to the conventional electrolytes recently 17 19 . Their porous structure offers a large effective surface area, capable of accommodating a large number of mobile protons 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, one-step self-assembly deposition method was developed for low-voltage oxide-based EDL transistors fabrication, and synaptic behaviors were mimicked in the IZO-based EDL transistors gated by nanogranular Manuscript SiO 2 electrolyte films [9], [10]. In addition, low-cost solutionprocessed chitosan proton conducting electrolyte film was also used as the gate dielectric for low-voltage oxide-based EDL transistor fabrication [11], [12]. In this letter, short-term potentiation and long-term potentiation is mimicked in such IZO-based EDL transistors gated by chitosan films.…”
Section: Introductionmentioning
confidence: 99%